Design of microwave bandpass filter with novel parallel coupled grooved microstrip structure - Marimuthu, Jayaseelan (2004)
The research consists of two parts. The first part is the derivation of the design equations for parallel coupled bandpass filter whilst the second part is the modification of the structure to improve the 2nd harmonic rejection. Physical dimension equations by Sina Akhtarzad, Thomas R. Rowbotham and Peter B. Johns [18], 1975 were modified to calculate the strip width-to-substrate thickness and like gap-to-substrate thickness ratios from desired values of the even and odd modes characteristic impedances. The modified equations were taken from [12] and [20]. The improved set of equations has accuracy of less than 1.5% and 4% for the even and odd mode characteristic impedances, respectively, compared to [17]. Each length of the coupled region is calculated by using the modified equation of [22]. The designed filter has accuracy of less than 1.64 % and 0.18% for the return and insertion losses, respectively, compared to the design from [17]. Conventional parallel coupled bandpass filter showed very high 2nd harmonic signal at twice the center frequency and asymmetrical response at the upper and lower stop bands. To improve the 2nd harmonic rejection and asymmetrical response at the upper and lower stop bands a modified structure of parallel coupled bandpass filter is proposed. The modified structure is very simple since it does not require recalculation of the physical dimension but showed very good improvement of the 2nd harmonic rejection. The modification was carried out by introducing consecutive square grooves in the arm of the coupled resonator of parallel coupled bandpass filter. The square grooves were placed at equal distance from each other where this ranges from 1 groove up to 7 grooves. The second harmonic present of the in the parallel coupled bandpass filter is due to the different phase velocity experienced by the even and odd modes. For the odd mode, the propagation on in the inner part of the parallel coupled line travels at high phase velocity compared to the even mode which travels at the outer part. By placing the square grooves at the inner part of the parallel coupled, this equalizes the electrical length for the odd and even modes. Hence, the rejection of 2nd harmonic and the improvement in the asymmetrical response were also achieved. The maximum rejection of -100dB for the 2nd harmonic and 30% improvement of the upper cut off frequency have been achieved